Estimation of Remogliflozin Etabonate Active Pharmaceutical Ingredient by Reverse Phase High-Performance Liquid Chromatography Method and Characterization of its Degradation Products by Liquid Chromatography-Mass Spectrometry - Somase, Kanchan P. (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: A reverse phase high-performance liquid chromatography (RP-HPLC) approach that is simple, sensitive, exact, and specific has been developed and verified for Remogliflozin Etabonate (REM) estimation. Materials and Methods: Using an isocratic mode methodology, the RP-HPLC procedure was run on a reversedphase kromasil C18 column (250 mm × 4.6 mm i.d., 5 μm i.d). The detection wavelength was kept at 228 nm and mobile phase consisting of Acetonitrile: 0.1% ortho phosphoric acid in water (60:40). The mobile phase flow rate was maintained at 1 mL/min. For REM, the retention period was 5.5, within the concentration range of 80–120 μg/mL. Results and Discussion: The technique showed linearity with a correlation coefficient (r2) of 0.997. The determined limit of detection and limit of quantitation was 0.186 and 0.563, respectively. In accordance with international conference on harmonization Q2 (R1) guidelines, the suggested approach was verified for linearity, accuracy, precision, and robustness. Studies on forced deterioration were conducted to identify a potential degradation mechanism. There was a noticeable difference in the retention period value between the pure drug peak and the degraded product peak, which could be clearly distinguished. The drug was found to be highly sensitive to acid, base hydrolysis, and peroxide conditions. Degraded products were subjected to mass spectral studies and the m/z values were identified for corresponding degradation products. Conclusion: The created technique can be applied to regular quality control assessments of REM and stability sample analysis.